PELAKSANAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA SMP NEGERI 3 TELUK KUANTAN - Maria Yulianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The background of this study was the low student learning outcomes of PPKn, from 28 students who achievedthe completeness criteria at least only 11 students (39.29%). The low student learning outcomes are caused bythe high level of individuality between students so that the achievement of competence among studentsexperiences a very distant difference. Based on this, the researchers made improvements to student learningoutcomes through the application of STAD cooperative learning models. This research is a classroom actionresearch, with the subject of class VII of SMP Negeri 3 Teluk Kuantan. The data used in this study is PPKnlearning outcomes data. The results stated that after applying the STAD type cooperative learning model studentlearning outcomes had increased in the initial data the number of students who completed were 11 students, incycle I had an increase with the number of 18 students, and in cycle II the number of students who completedcontinued to increase by the number 22 student.